Monitoramento remoto aplicado a um veículo elétrico - Santos Junior, Eduardo dos (2023)
This document presents the development of a remote monitoring system applied to an electric vehicle prototype, developed by the Tubarão Branco energy efficiency team. The goal of the system is to collect data generated by the prototype during its operation and wirelessly transmit it to a computer, where it will be displayed graphically. Communication between the prototype devices is performed through a CAN bus, and this work proposes the development of an internal device within the vehicle to read the data from the CAN bus and transmit it using LoRa technology to an external device. This external device, in turn, transmits the data to a computer, where it will be processed and displayed in graphs using the Python programming language. The generation of graphs from the collected data aims to provide a detailed analysis of the vehicle’s performance during the journeys undertaken in competitions. This provides greater safety for the pilot and assists the team in seeking improvements and optimizations for the vehicle. It is worth noting that, if more devices are added to the vehicle, the project can be easily expanded by the team members. Throughout this document, the devices used in the system, details of their implementation and operation, and the methodology adopted for data collection and analysis will be presented.